S-ADEMETHIONINE ROLE IN SUPPORTIVE TREATMENT OF ACUTE MYELOBLASTIC LEUKEMIA - Skrypnyk, I.M.; Maslova, G.S. (World of Medicine and Biology, 2019)
The article presents the results of our own studies to assess the frequency and nature of the of of the liver functional disorders development in patients with acute myeloid leukemia, as well as the feasibility of prescribing S-ademethionine against the background of chemotherapy as part of the supportive care. Development of hepatotoxic reactions was recorded on the 7th day of chemotherapy in 32.1% (9/28) of group I patients who received only chemotherapy, and in 4.2% (1/24) of group II patients who were additionally prescribed S-ademethionine. Hepatotoxic reactions during chemotherapy for acute myeloid leukemia in 22.2% (2/9) patients corresponded to the cytolytic type, 44.4% (4/9) to the cholestatic type, and 33.3% (3/9) to the mixed type. On the 28th day of observation, the recurrence of hepatotoxic reactions was recorded. It has been proven that inclusion of S-ademethionine into the treatment of acute myeloid leukemia chemotherapy is associated with a reduced risk of hepatotoxic reactions (RR = 0.13; 95% CI = 0.018-0.95; p
Keywords: acute myeloid leukemia; chemotherapy; hepatotoxic reactions; S-ademethionine